The frontiers of management - Drucker, Peter F. (Peter Ferdinand), 1909-2005. (Boston : Harvard Business Review Press, 2010)
Discusses the new economic forces that affect lives and livelihoods, today's changing people and their workplace surroundings, the newest management concepts and practices, and the shape of evolving organizations as they respond to increasing tasks and responsibilities.
Preface : the future is being shaped today -- Interview : a talk with a wide-ranging mind -- The changed world economy -- America's entrepreneurial job machine -- Why OPEC had to fail -- The changing multinational -- Managing currency exposure -- Export markets and domestic policies -- Europe's high-tech ambitions -- What we can learn from the Germans -- On entering the Japanese market -- Trade with Japan : the way it works -- The perils of adversarial trade -- Modern prophets : Schumpeter or Keynes? -- Picking people : the basic rules -- Measuring white-collar productivity -- Twilight of the first-line supervisor? -- Overpaid executives : the greed effect -- Overage executives : keeping firms young -- Paying the professional schools -- Jobs and people : the growing mismatch -- Quality education : the new growth area -- Management : the problems of success -- Getting control of staff work -- Slimming management's midriff -- The information-based organization -- Are labor unions becoming irrelevant? -- Union flexibility : why it's now a must -- Management as a liberal art -- The hositle takeover and its discontents -- The five rules of successful acquisitions -- The innovative organization -- The no-growth enterprise -- Why automation pays off -- IBM's Watson : vision for tomorrow -- The lessons of the bell breakup -- Social needs and business opportunities.
"Where tomorrow's decisions are being shaped today"--Jkt.
Includes index.
Keywords: Management; Industrial management